Predictors of sudden cardiac arrest in adolescents with mitral valve prolapse: an analysis of the nationwide inpatient sample. (25th November 2020) - Narasimhan, B; Wu, L; Lucas, C.H; Bhatia, K; Shah, A; Kantharia, B
Abstract: Background: Mitral valve prolapse (MVP) is the most commonly encountered valvular pathology seen in 2–3% of the general population. Though traditionally regarded as a benign pathology, recent literature suggests that sudden cardiac death is significantly more common in these patients with estimates of 0.2–0.4%/year. The exact underlying mechanism of these higher rates of SCD remain poorly understood. In this study, we aim to identify predictors of sudden cardiac arrest (SCA) in an adolescent population. Methods: We conducted a retrospective study using the AHRQ-HCUP National Inpatient Sample 2016-2017 for the years 2016-17. All patients (≤18 years) admitted with Mitral valve prolapse were identified using ICD-10 codes and further sub stratified based on presence or absence of sudden cardiac arrest (SCA). Baseline characteristics were obtained and multivariate regression analysis was utilized to identify potential predictors of SCA. Independent risk factors for in-hospital mortality were identified using a proportional hazards model. Complications were defined as per the Agency for Health Care Research and Quality guideline. Results: We screened a total of 71, 473, 874 admissions in the NIS database to identify a total of 1, 372 adolescent patients admitted with MVP in the years 2016–17. These patients were then sub-categorized based on presence or absence of SCA during the hospitalization. Our findings revealed that patients with SCA were generally slightly older (15y vs 13y, p=0.036, OR-1.1, p=0.007) and more likely female (83.3% vs 13%, p=0.227, OR – 3.55, p=0.57)). Interestingly, patients in the SCA cohort were noted to have almost 4 fold higher rates of Mitral regurgitation (66.6% vs 18.35%, p=0.008, OR-8.89, p=0.005) as well as family history of SCD (16.7% vs 4.1%, p=0.145, OR-4.65, p=0.14). Conclusions: Presence of Mitral regurgitation and a family history of sudden cardiac death are associated with significantly higher rates of SCA in adolescent patients with mitral valve prolapse. Funding Acknowledgement: Type of funding source: None